Temperature-responsive copolymers without compositional drift by RAFT copolymerization of 2-(acryloyloxy)ethyl trimethylammonium chloride and 2-(diethylamino)ethyl acrylate. Issue 17 (27th February 2019) - Rodrigues, Ana Sofia; Charreyre, Marie-Thérèse; Favier, Arnaud; Baleizão, Carlos; Farinha, José Paulo S.
Abstract : Thermoresponsive copolymers based on AEtMACl and protonated DEAEA feature RAFT copolymerization kinetics with both apparent reactivity ratios of about 1. Abstract : We prepared novel temperature and pH responsive copolymers of [2-(acryloyloxy)ethyl] trimethylammonium chloride (AEtMACl) and 2-(diethylamino)ethyl acrylate (DEAEA) by RAFT polymerization. Such copolymers show a volume phase transition temperature that explains the excellent performance of hydrogels of the same monomers, selected among 600 different monomer combinations, to release cultured stem cells using only a mild temperature stimulus (R. Zhang, H. K. Mjoseng, M. A. Hoeve, N. G. Bauer, S. Pells, R. Besseling, S. Velugotla, G. Tourniaire, R. E. B. Kishen, Y. Tsenkin, C. Armit, C. R. E. Duffy, M. Helfen, F. Edenhofer, P. A. Sousa and M. Bradley, Nat. Commun., 2013, 1–10). We carried out a thorough investigation of the (co)polymerization kinetics of AEtMACl and protonated DEAEA in ethanol, and proposed convenient and reliable methods to follow the conversion of these two monomers by 1 H NMR. Interestingly, for a very large range of feed compositions, the cumulative copolymer composition versus global conversion plots indicated that there was almost no compositional drift, corresponding to apparent reactivity ratios of about 1. Therefore, the copolymer has the same composition as the comonomer feed, regardless of both conversion and initial molar ratio. This rare situation enables the preparation of a variety of copolymer chains with highly homogeneous composition and microstructure, offering excellent prospects for the use of these materials as triggers in controlled release applications.